Det offentliga rummet - Weibull, Eva (2010)
‘What is happening with open public space?’ and ‘Why is it happening now?’ are the two overarching questions in this master thesis. In the essay the concept of ‘offentligt rum’ (open public space) is defined as an exterior place accessible to the general public, such as squares, parks and streets. I have, based on the issues, identified the trends and tendencies of open public space in Sweden. The study consists of three sections. The first one is the most comprehensive and consists of a text study. Texts were studied from Boverket (The national Board of Housing, Building and Planning), Movium (Centre for the Urban Public Space at the Swedish University of Agricultural Sciences) and the Swedish journals Arkitektur, Arkitekten and Plan. The studied texts were published from 2007 to 2010. The second part consists of two interviews. Both the interviewees work with public space on a daily basis. The third part is an indepth look into the city of Malmö with public space and consists of an interview with a landscape architect at the municipality. The studied texts are presented in the essay in six identified topics. The trends and tendencies of the open public space have been expressed within these topics. A discussion based on the text study and the three interviews then follows, which explores comprehensive trends and tendencies of the open public space. The question ‘Why is it happening now?’ is also discussed based on the three interviews.